2021
DOI: 10.1021/acs.jpclett.1c03409
|View full text |Cite
|
Sign up to set email alerts
|

Highly Polarized Upconversion Emissions from Lanthanide-Doped LiYF4 Crystals as Spatial Orientation Indicators

Abstract: Polarized emission, an inherent characteristic that correlated with structure and morphology, is very sensitive to orientation. For the upconversion (UC) emission of lanthanides, the mechanism of polarization is rarely discussed, and the highly polarized UC emissions are poorly developed. Herein, with the benefit of the strong anisotropic crystal field, well-resolved emissions from lanthanide-doped LiYF 4 crystals were studied, and highly polarized UC emissions from Er 3+ and Ho 3+ were investigated. With mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Accordingly, the corresponding polarization emission profile yielded a fitted curve in the shape of the number “8”. The long axis of the fitted polarization emission profile was in accordance with the oriented direction of the molecular transition dipoles ( μ ) of the crystal under study [ 39 , 40 , 41 , 42 ]. In other words, when the electric field of the light was parallel to μ , the emission was the highest ( I max ), while the emission was the lowest ( I min ) when the electric field was vertical to μ .…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Accordingly, the corresponding polarization emission profile yielded a fitted curve in the shape of the number “8”. The long axis of the fitted polarization emission profile was in accordance with the oriented direction of the molecular transition dipoles ( μ ) of the crystal under study [ 39 , 40 , 41 , 42 ]. In other words, when the electric field of the light was parallel to μ , the emission was the highest ( I max ), while the emission was the lowest ( I min ) when the electric field was vertical to μ .…”
Section: Resultsmentioning
confidence: 81%
“…The variation of the positions of the pyridine nitrogen atoms on the skeleton allows for the formation of hydrogen bonds between pyridinium protons and sulfonate anions in different directions. In addition, the polarized emission properties of organic crystals are highly dependent on the molecular arrangement, and those with consistent parallel or antiparallel molecular orientation generally display a high degree of emission polarization [ 39 , 40 , 41 , 42 ]. On account of the highly ordered binary molecular packing in two-component linear hydrogen-bonded polymers, the fabricated microcrystals are expected to display prominent polarized emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, obtaining linearly polarized light required the installation of bulky and rigid optical components such as polarizers, which increased the optical loss and limited its application. , Therefore, polarization-sensitive materials with inherent polarized photoluminescent emissions have gained tremendous attention. In this context, optical anisotropy is the cornerstone of polarized luminescence, as it can affect the light transmission and absorption properties, which is also closely correlated with crystallographic symmetry, morphology, or configuration. Recently, the emerging 2D anisotropic materials became promising due to their intrinsic sensitivity to linearly polarized light. ,, However, 2D materials with high polarization anisotropy are still rare to date, particularly for combined short-lived and long-lived polarized emission in one system.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, some other groups also reported the polarized UCL from NaYF 4 , LiYF 4 , and LiLuF 4 UCNPs. [107][108][109][110][111] To make use of polarized UCL, Paloma et al reported using microsized upconverting particles (UCP) to monitor the suspending medium in real-time via singleparticle spectroscopy. [112] Single UCP was optically trapped and maintained at a certain position, followed by the excitation of linearly polarized 980 nm laser (Figure 10b).…”
Section: Regulating Upconversion By Different Polarization Anglementioning
confidence: 99%